Investigation into the Interrelation Between Parenting Styles and Parental Financial Behavior - Ndou, Adam (Universitas Djuanda, 2024)
Parenting styles are an essential factor in how parents raise their children. More literature is needed about the role of parenting styles on parental financial socialization. How parents manage their finances is essential as children observe and imitate their parents' behavior. This study investigated the relationship between parenting styles and parental financial behavior. Parenting style was measured through authoritarian, neglectful, authoritative, and permissive. This study adopted a quantitative research approach and used a self-administered questionnaire to collect data from young adults in two provinces (Gauteng and Mpumalanga) in South Africa. Correlation analysis was used to analyze data. The results showed a significant positive relationship between authoritarian, neglectful, authoritative, and permissive parenting styles and parental financial behavior. Thus, it is concluded that a significant positive relationship exists between parenting styles and parental financial behavior. The study implies that parents should invest more time in understanding and evaluating their parenting styles and adopt authoritarian, authoritative, and permissive parenting styles as they were found to support and foster financial socialization. Financial educators and the government must design and implement financial programs to inform parents of different parenting styles. This study contributes to the existing body of knowledge by empirically testing the relationship between parenting styles and parental financial behavior.